Development and evaluation of an interprofessional teaching concept for modern wound management - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Background and objectives: The aim of the present study was to establish and evaluate a new interprofessional teaching concept on the topic of wound management. Methods: After determining the status quo using a survey among medical students, we developed a new teaching concept that included a 150-minute course aimed at providing students with the opportunity to gain hands-on wound management skills. This interprofessional course was offered at the existing ‘SkillsLab’ teaching facility. The participants’ subjective level of knowledge was assessed by questionnaire before and after the course. Results: Our survey among 190 medical students showed them to be very interested in gaining practical experience in the field of wound management. To date, 120 participants (54.8 % medical students; 45.2 % nursing students) have attended this new interprofessional course, which has been equally well received by both medical and nursing students. For all specific topics (diagnosis, treatment, use of wound dressings, debridement), course participation was associated with a significant increase in knowledge. Conclusion: Given its relevance in clinical practice, it is important for medical students to learn about the various aspects associated with the care of patients with chronic wounds. By offering new teaching concepts, dermatology in particular is well suited to help students gain a better understanding of the challenges related to wound management and to improve their practical skills. Wound management is an ideal topic for interprofessional learning.
CRIS-Team Scopus Importer:2020-09-11

Entwicklung und Evaluation eines interprofessionellen Lehrkonzepts zum modernen Wundmanagement - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-10-09

TIP – Training of Intensive medical support in the case of a Pandemic - Lütcke, Björn; Günther, J.; Köhnen, Julia; Puchinger, A.; Schmidt, Anita (GMS Journal for Medical Education, 2021)
The COVID-19 pandemic has led to a short-term sharp increase in the demand for auxiliary staff in emergency rooms and intensive care units. Against this background student tutors of the Medical Faculty Erlangen have developed a training concept. The aim was to familiarize students in the clinical section quickly and effectively with skills that are particularly important in a clinical assignment as (student) assistant in the care of corona patients (e.g.: personal protective equipment, intubation assistance, arterial blood collection, assessment of blood gas values and ventilation parameters). In a blended learning concept, learning materials were prepared in ad-vance and then implemented and deepened in a presence phase. The selection of learning materials and the low supervision ratio (1:2) made it possible to realize an internally differentiated approach. The offer met with great interest among students of all clinical semesters and was evaluated very positively. The skills learned can be applied widely even independently of a pandemic.
CRIS-Team Scopus Importer:2021-03-05
Keywords: COVID-19; Internal differentiation; Peer-teaching; Self-protection